Impact of Climate Change to the Total and Peak Energy Demands of a Northern Finnish Building by 2050 - Louis, Jean-Nicolas; Pulkkinen, Jari (Zenodo, 2019)
Climate change increases the outdoor temperatures in the future, modifying the energy demand of the buildings from today. As the new buildings are constructed to last, they should take the impact of climate change into account during their design phase. The objective of this study is to investigate the changes in total and peak energy demands in buildings having different levels of thermal insulation, to explore if the impacts of climate change are similar to all selected building types by 2050. The impact of climate change to the weather data is gathered from different climate change projections to achieve a comprehensive analysis of the possible future directions. The new weather files are created using ‘morphing’ method and using meteorological test reference year for building simulation and measured weather data for constructing the future weather files. The results indicate that the energy demand will decrease by 4-8% in passive building type by 2050, with heating demand decreasing 4-10% and by starting to have cooling demand in A1B, A2 and RCP8.5 scenarios for passive building. The scenarios with higher projections for temperature increase also have larger decreases in total energy demands indicating that the starting of having cooling demand does not overcome the decrease in heating demand. Moreover, the peak demand for heating is projected to decrease in the future, but at the same time peak cooling demand starts to occur, which may need to be taken into account in the future energy system.